A comparison of visual function scores in hydrocephalic infants with and without lumbosacral myelomeningocoele (2002)
Purpose: The cerebrum is frequently malformed in children with myelomeningocoele. This anomaly renders them potentially susceptible to cerebral visual impairment. In these patients, hydrocephalus is an important and frequent complicating lesion which compromises intellectual function and may also cause cerebral visual impairment. In this study, we determined whether hydrocephalic patients with lumbar myelomeningocoele (HLM) are at a greater risk of visual impairment than hydrocephalic patients without this lesion (H). Methods: In this prospective study, we assessed five parameters of visual function in 20 hydrocephalic children with lumbar myelomeningocoele and compared the total visual function scores (TVFS) obtained with those from hydrocephalic children without overt spinal dysraphism, but similar in age, sex and ventricular size. The parameters, which were assessed with the aid of a quantitative grading scale, were papillary size and reaction, optic atrophy, visual fixation and tracking. Results: The age and sex distributions of the patients in the two groups were similar. The anterior and posterior dimensions of the lateral ventricles were also similar. The mean (SD) of the TVFS were 24.25 (3.63) and 24.20 (3.47) respectively for the two groups (P = 0.90). Conclusions: The results suggest that, in hydrocephalic infants with lumbar myelomeningocoele, visual function is not further diminished by the associated dysraphism and that ventricular dilatation is the major determinant of visual impairment.